The Effect Of Communication And Work Environment On Employee Performance With Motivation As Intervening Variable At Royal Prima Medan Hospital - Mikael, Mikael; Sofiyan, Sofiyan; Faris, Salman; Fitri Rostina, Cut (International Journal of Science, Technology & Management, 2022)
This study aims to determine whether communication and work environment affect employee performance through job satisfaction as an intervening variable at Royal Prima Hospital Medan. The study was conducted on 105 non-medical employees of Royal Prima Hospital Medan using saturated sampling technique. The data collection technique used is primary data in the form of questionnaires and secondary data obtained through documentation studies. The data analysis technique uses quantitative data which is processed with SPSS version 25 program, namely t test, coefficient of determination (R2) and path analysis. The results obtained in this study indicate 1) there is a significant influence between communication on motivation, 2) there is a significant influence between work environment variables on motivation, 3) there is a significant but not significant effect between motivational variables on performance, 4) there is a significant but not significant effect between communication variables on performance, 5) there is a significant influence between work environment variables on performance, 6) motivation variables can affect communication variables on performance, 7) motivational variables can affect work environment variables on performance. The ability of communication variables, work environment and motivation in explaining employee performance at Royal Prima Hospital Medan is 72.9%, while the remaining 27.1% is explained by other variables not included in this research model.